Comparative mapping, genomic structure, and expression analysis of eight pseudo-response regulator genes in Brassica rapa - Kim, Jin A; Kim, Jung Sun; Hong, Joon Ki; Lee, Yeon-Hee; Choi, Beom-Soon; Seol, Young-Joo; Jeon, Chang Hoo (Molecular genetics and genomics : MGG, 2012)
Circadian clocks regulate plant growth and development in response to environmental factors. In this function, clocks influence the adaptation of species to changes in location or climate. Circadian-clock genes have been subject of intense study in models such as Arabidopsis thaliana but the results may not necessarily reflect clock functions in species with polyploid genomes, such as Brassica species, that include multiple copies of clock-related genes. The triplicate genome of Brassica rapa retains high sequence-level co-linearity with Arabidopsis genomes. In B. rapa we had previously identified five orthologs of the five known Arabidopsis pseudo-response regulator (PRR) genes that are key regulators of the circadian clock in this species. Three of these B. rapa genes, BrPRR1, BrPPR5, and BrPPR7, are present in two copies each in the B. rapa genome, for a total of eight B. rapa PRR (BrPRR) orthologs. We have now determined sequences and expression characteristics of the eight BrPRR genes and mapped their positions in the B. rapa genome. Although both members of each paralogous pair exhibited the same expression pattern, some variation in their gene structures was apparent. The BrPRR genes are tightly linked to several flowering genes. The knowledge about genome location, copy number variation and structural diversity of these B. rapa clock genes will improve our understanding of clock-related functions in this important crop. This will facilitate the development of Brassica crops for optimal growth in new environments and under changing conditions.